VD_FINDINFO 204/II vom 15. Oktober 2009 - VD Tribunal cantonal (2009)
OBLIGATION D'ENTRETIEN, MINIMUM VITAL, ATTEINTE À LA SANTÉ, TRANSPORT | 125 CC, 138 al. 1 CC, 451 ch. 2 CPC, 452 al. 2 CPC, 465 al. 1 CPC